2009
DOI: 10.1021/ja901392s
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of Conductive Polymers To Modulate Superoleophobic Properties

Abstract: Natural surfaces can be superhydrophobic, but on the other hand, superoleophobic properties are extremely rare. We demonstrate that modification of the 3,4-alkylenedioxy bridge length in pyrrole-derivative monomers can have a dramatic influence on the superoleophobic properties of electrodeposited conductive polymers. Here we report the synthesis and characterization of novel fluorinated 3,4-ethylenedioxypyrrole (EDOP) and 3,4-propylenedioxypyrrole (ProDOP) monomers and their corresponding electrodeposited pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
130
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(131 citation statements)
references
References 90 publications
0
130
1
Order By: Relevance
“…We use two different kinds of SHSs with ultralow hysteresis and sliding angle that are obtained by electropolymerization. The first one is a superhydrophobic and superoleophobic fluorinated poly(3,4-ethylenedioxypyrrole) [17] and the second one a superhydrophobic fluorinated polyfluorene [18]. Their low hysteresis and sliding angles, less than 2.0 degrees, are due to the combination of microstructures and nanostructures/nanoporosities with the low surface energy of the fluorinated chains.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…We use two different kinds of SHSs with ultralow hysteresis and sliding angle that are obtained by electropolymerization. The first one is a superhydrophobic and superoleophobic fluorinated poly(3,4-ethylenedioxypyrrole) [17] and the second one a superhydrophobic fluorinated polyfluorene [18]. Their low hysteresis and sliding angles, less than 2.0 degrees, are due to the combination of microstructures and nanostructures/nanoporosities with the low surface energy of the fluorinated chains.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…74,75 After that, they synthesized novel fluorinated monomers and their corresponding electrodeposited polymers with superoleophobic property. 65,[76][77][78] The nanoporous structures [ Fig. 4(B)] and the low surface energy of the monomer are the key reasons for the superoleophobicity.…”
Section: Electrochemical Polymerization and Electrochemical Depositionmentioning
confidence: 99%
“…Conductive superoleophobic surfaces are mainly prepared by electrochemical polymerization using fluorinated monomers. Nicolas et al, 65,[73][74][75][76][77][78] Yan et al, 79 and Chiba et al, 80 have reported a series of work on preparation of highly fluorinated conductive polymers with superoleophobicity by this method, which have been discussed in Fabrication of Polymer Superoleophobic Surfaces. Das et al developed a simple method to prepare large-area electrically conducting films with super oil-repellent property.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…21,22 Although significant progress has been achieved for membrane-based oil/water separation in the last few years, development of separation membranes for organic liquids is still highly limited because organic liquids usually possess a relatively lower surface tension than water. The difficulty in separation of organic liquid mixtures has increased because it is more difficult to build a superoleophobic [23][24][25][26][27][28][29] material than a superhydrophobic material. We recently proposed an oleophobicity-tunable TiO 2 nanofibrous membrane prepared by electrospinning, calcination and a subsequent chemical modification method that achieved immiscible organic liquids separation.…”
Section: Introductionmentioning
confidence: 99%